PENGARUH FINANCIAL STABILITY, EXTERNAL PRESSURE, INEFFECTIVE MONITORING, CHANGE IN AUDITOR,CHANGE IN DIRECTOR DAN FREQUENT NUMBER OF CEO’S PICTURE TERHADAP FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD PENTAGON (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI Tahun 2011-2016) - Vivi Rizkiana Aprilla; R Adri Surya; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to obtain empirical evidence about the effectiveness of the fraud pentagon in detecting financial statement fraud. The element of the fraud pentagon that is used as independent variables is a pressure with proxy financial stability (ACHANGE) and external pressure (LEV), opportunity with proxy ineffective monitoring (BDOUT), rationalization with proxy the change in auditor (CPA),capability with proxy change in director (DCHANGE) and arrogance with proxy frequent number of CEO’s picture. In this research uses a proxy earnings management with discretionary accruals as the dependent variable. The population of this research is the manufature companies listed in Indonesia Stock Exchange in 2011-2016. Total sample of this research is 89 companies with six years observation.Data analysis was performed with the classical assumption and hypothesis testing using multiple linear regression. The results indicates that the financial stability (ACHANGE),the change in auditor (CPA), the change in director (DCHANGE), and the frequent number of CEO’s picture (CEOPIC) influence the financial statement fraud. Meanwhile, the external pressure (LEV) and ineffective monitoring (BDOUT) has no significant impact on financial statement fraud.The influence of the independent variables to describe the dependent variable is 32,1%, while the remaining 67,9% is influenced by other variables.Keywords : Financial Statement Fraud, Earnings Management, Fraud Pentagon